ICT Access and Entrepreneurship in the Open Innovation Dynamic Context: Evidence from OECD Countries - Sofia Gomes; João M. Lopes (Journal of Open Innovation: Technology, Market and Complexity, 2022)
ABSTRACT: In recent decades, entrepreneurship has become increasingly important for innovation and economic growth. However, few studies demonstrate the role of information and communication technology systems (ICT) in promoting entrepreneurship, and even fewer studies show that ICT is a crucial resource for entrepreneurs. This study examines the direct influence of ICTs on entrepreneurial activity in OECD countries in the context of the open innovation dynamic. Based on an unbalanced dynamic longitudinal panel of data, we conclude that access to ICTs (mobile-cellular telephone subscriptions, individuals using the internet, and fixed-broadband subscriptions) positively influences Total early-stage Entrepreneurial Activity (TEA). However, the importance of ICTs for entrepreneurial activity is not equal, with mobile-cellular telephones having the strongest influence on the rate of new firm creation, followed by fixed-broadband, and internet access. This study contributes to the rationale of resource-based theory by demonstrating that ICTs are a valuable resource for boosting the capabilities for creating, collecting, processing, and interpreting information, which is vital for entrepreneurial activity. On the other hand, this study attempts to suppress an existing gap in the literature due to the still scarce studies demonstrating how macro-level ICTs affect the creation of new firms in countries. Finally, it contributed to empirically substantiating the relationship between open innovation dynamic and entrepreneurship, as very few studies do.